Pemberian Jus Nanas (Ananas cosmosus) Terhadap Lama Penyembuhan Luka Perineum Pada Ibu Post Partum - Tobing, Suryati Romauli; Yogi, Ruth; Lestari, Muji (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2026)
Almost all initial childbirths witness perineal tears, and these occurrences are not uncommon in subsequent deliveries. Complications, such as puerperal infections (including vaginitis, vulvitis, endometritis, and cervicitis), may arise from inadequate treatment of perineal wounds. To enhance the healing process of these wounds, the use of pineapple juice (Ananas Cosmosus) as a complementary therapy has been suggested. This study aims to evaluate the effects of consuming pineapple juice on the recovery time of perineal wounds in postpartum mothers at the Putri Clinic in Jayawijaya Regency. Employing a quantitative approach with a quasi-experimental design, the research utilizes the Posttest Only Control Group design, where the experimental group will be given perineal wound treatment by consuming pineapple juice (Ananas Cosmosus) while the control group does not get treatment. The study encompassed a population of 80 spontaneous postpartum mothers experiencing perineal rupture at levels II and III, treated at the Putri Clinic. A total of 42 respondents were selected through axial sampling, following the inclusion criteria. Data collection involved identity sheets and perineal wound observation sheets, while analysis utilized the Mann Whitney test, a non-parametric statistical test. Findings revealed that in the control group, where pineapple juice was not administered, the majority experienced a slow healing process, exceeding 7 days (73.3%). Conversely, in the intervention group receiving pineapple juice, all participants exhibited a swift healing process, completing in less than 6 days (100%). The Mann Whitney test results indicated statistical significance, with Asig (2-tailed) = 0.000 < 0.05.